2008
DOI: 10.1186/1745-0179-4-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between anxiety, depression and illness perception in tberculosis patients in Pakistan

Abstract: ObjectiveAs the rates of TB world over have increased during the past 10 years, there has been a growing awareness of depression and its role in the outcome of chronic disorders. Though depression is common in patients with TB no study as yet has examined the prevalence of depression in this group in Pakistan. We aimed to determine the presence of depression, anxiety and illness perceptions in patients suffering from Tuberculosis (TB) in Pakistan.Methods108 consecutive outpatients with tuberculosis completed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
89
4
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 19 publications
15
89
4
4
Order By: Relevance
“…From the total female population, depression cases were 25% which was higher than 15.87% in male where it was comparable to literatures [8][9][10][11][12][13][14][15]. Depression was higher in widowed being 36.36% which was comparable with other data [10].…”
Section: Discussionsupporting
confidence: 88%
“…From the total female population, depression cases were 25% which was higher than 15.87% in male where it was comparable to literatures [8][9][10][11][12][13][14][15]. Depression was higher in widowed being 36.36% which was comparable with other data [10].…”
Section: Discussionsupporting
confidence: 88%
“…The data was based on comparative studies of TB population from China , two from Malaysia [18,23], five from India [14,15,29,[35][36][37][38], four from Canada [5,24,25,30] one form each UK [17] Pakistan [35], Spain [36] Taiwan [28] South Africa [37] and Turkey [39]. Among the selected articles fourteen studies were cross sectional [5,14,26,27,30,33,[34][35][36][37][38][39][40] and sixteen were prospective cohort based studies [15][16][17][18][19][20][21][22][23][24][25][26]29,31,32,41]. An article published by Chamla et al …”
Section: Summary Of Resultsmentioning
confidence: 99%
“…But among TB patients, prevalence of anxiety was lower than internally displaced Jaffna population (32.6%) and depression was lower than patients with MI [5,8]. A study done in Pakistan using similar scales had shown that 46% depression and 47% anxiety among patients with TB [6]. Our study exclude doubtful cases in HADS-A (22.6%) and HADS-D (21.9%) scales which suggests the true prevalence of depression and anxiety among TB patients may be higher.…”
Section: Discussionmentioning
confidence: 97%
“…Also, prevalence of depression was 22.2% and anxiety was 32.6% among internally displaced persons in post-war Jaffna District [5]. Studies have shown an association between TB and common mental disorders (46.3%-80%) [6]. The selfregulation model suggests that the illness beliefs of individuals guide their coping strategies.…”
Section: Introductionmentioning
confidence: 99%